PENYELESAIAN PERSELISIHAN ADAT ISTIADAT DALAM KEHIDUPAN MASYARAKAT DI KABUPATEN ACEH BARAT BERDASARKAN TINJAUAN PERATURAN GUBERNUR ACEH - Nellis Mardhiah (Prodi Sosiologi FISIP Universitas Teuku Umar, 2016)
The aim of this study was to know the customs and traditions of dispute mechanism in community life of Gampong Baroh Pasi Aceh, Meurebo District, West Aceh. The methodology of the study was intentionally used a phenomenological approach in order to understand social phenomena in the life of the community in resolving the conflict. The subjects were in-depth interviews with village officials and traditional leaders in getting information by assuming the social cases show that the problem is not solved by custom. The research results of Governor Regulation No. 60 Year 2013 on Implementation Grievance /dispute customs and traditions in the Gampong Pasi Aceh Baroh, Meureubo District, West Aceh has not run optimally, it can be seen in the attitude of people who prefer the legal system in solving the problem of settlement through traditional institutions, especially in Gampong Baroh Pasi Aceh, Meureubo District, West Aceh. In addition, the government of Gampong Pasi Aceh Baroh to act as traditional authorities has not yet fully understand and know about the presence of the gubernur of regulation No. 60 Year 2013 on implementation of dispute resolution/dispute customs and ceremonies in Gampong Pasi Aceh Baroh, Meureubo District, West Aceh. In conclusion, the Gampong Pasi Aceh Baroh must fully understand that the traditional dispute resolution have gotten as few as follows: first, custom solution for cheap and filled with elements of familiarity; and second, custom solution for legally binding and recognized by the formal legal institutions based on the rule of governor.Key Word : Settlement of Disputes, Customs, Government of the village.